Telecommunication Mergers and Acquisitions: An Event Study Analysis - Agarwal, Hemant (2008)
The change in global communications in the past decade has been remarkable, bringing fundamental changes in the structure and the regulation of telecom markets worldwide. Leading edge technology and liberal telecom solutions have caught the eye of several telecommunication manufacturers, service providers, and operators. This dissertation describes the various telecommunication mergers undergone in the USA and the UK in the past ten years. For this purpose An event study approach is used to study the performance of the acquiring company surrounding the days of the merger and acquisition announcement.